Catálogo das plantas ruderais da cidade de Curitiba, Brasil. Estudos preliminares III - Cervi, Armando C.; Guimarães, Olavo A.; Acra, Luiz A.; Negrelli, Raquel R. B.; Sbalchiero, Denise (Acta Biológica Paranaense, 1988)
Catálogo das plantas ruderais da cidade de Curitiba, Brasil. Estudos preliminares III